Dancing Culture Religion. (Studies in body and religion., 2012)
In this provocative study of dancing, Sam Gill examines the interpretive styles of a variety of cultural dance traditions in discourse with the philosophic traditions of Schiller, Merleau-Ponty, Barbaras, Derrida, Leroi-Gourhan, and Baudrillard. As a scholar of religion, Gill provides special consideration to the importance of this emerging appreciation of dancing as a perspective inclusive of body and experience. Each chapter delves into the many factions of dancing: moving, gesturing, self-othering, playing, seducing, and masking. Gill also draws on the analysis of contemporary dance films and musicals, his experience as a dancer and dance teacher, his extensive research on dance traditions, and his interest in neurobiology and phenomenology to develop the core of this rich exploration of "dancing," the structurality of all dances.